Implication of Fertilizers-Subsidy Withdrawal: Implications of Subsidy Withdrawal on GDP, Food Security, and Agricultural Economy (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Previous chaptersmay prompt one to conclude that fertilizer subsidy withdrawal is inevitable. Itis a matter of time when it is either completely withdrawn or its present shapegoes under transformation much under budgetary pressure rather than the WTOobligations. The subsidy withdrawal will have many ramifications. It willimpact GDP both on supply and demand side besides denting farmer’s purchasingpower and food security in terms of physical availability. This chapter willanalyze the effect of subsidy withdrawal and experience of a few countriesabout subsidy elimination on the basis of selected studies.